Fenomena Fasakh Nikah di Era Kontemporer: Studi Perbandingan Mazhab al-Syafi’i dan Mazhab Hanafi - Muliani, Nini; Puyu, Darsul S (Universitas Islam Negeri Alauddin Makassar, 2023)
The purpose of this study is to find out the views of the al-Shafi'i school and the Hanafi school about the phenomenon of fasakh nikah on the grounds that the husband is poor in the contemporary era. This research uses a qualitative type of research, with data collection using library research methods, the approach method used is normative by examining the Qur'an and Hadith as the basis of Islamic law, primary data sources in the form of the Qur'an and Hadith while secondary data sources in the form of books, journals, and other scientific papers. The results showed that marriage on the grounds of the husband in the contemporary era according to the views of the al-Shafi'i school and the Hanafi school is first according to the al-Shafi'i school saying that if the husband is in a state of incapacity or in a poor state that cannot provide for his wife in the form of food, clothing, and shelter then the wife can and is allowed to file for divorce through a judge (fasakh). Secondly, according to Hanafi, when a husband is unable to provide a living, the wife is not allowed to use the right of fasakh to sue her husband for divorce. A husband who is unable to provide for his wife may be due to two things, first: because he is reluctant or unwilling to take responsibility as a husband even though he is able, second: the condition of the husband is indeed in a poor state so that the husband has not been able to provide for his wife. Imam Hanafi reasoned that the wife was not allowed to claim her rights (fasakh) because the husband's obligation was only to provide according to his ability, the husband was still given the opportunity to earn a living so that he could return to meet his wife's bread.